Utilitarian and retributive arguments for the death penalty under the Nigerian criminal justice system : towards the justification and desirability of the death penalty in a relational society - Chimakonam, Jonathan Okeke (University of Pretoria, 2023)
Thesis (PhD (Philosophy))--University of Pretoria, 2022.